2019
DOI: 10.1371/journal.pone.0219554
|View full text |Cite
|
Sign up to set email alerts
|

Desiccation-induced viable but nonculturable state in Pseudomonas putida KT2440, a survival strategy

Abstract: The potential of Pseudomonas putida KT2440 to act as a plant-growth promoter or as a bioremediator of toxic compounds can be affected by desiccation. In the present work, the bacterial survival ratio (BSR) in response to air desiccation was evaluated for P . putida KT2440 in the presence of different protectors. The BSR in the presence of nonreducing disaccharides, such as trehalose, was high after 15 days of desiccation stress (occurring at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 61 publications
0
33
0
Order By: Relevance
“…Viable but non-culturable (VBNC) cells have low metabolic activity and intact membranes, but they are unable to replicate until they enter a more hospitable environment ( Ayrapetyan et al, 2018 ). Pseudomonas strains can enter this state as a response to unfavorable environmental conditions such as nutrient limitation, temperature extremes, and desiccation ( Lowder et al, 2000 ; Arana et al, 2010 ; Pazos-Rojas et al, 2019 ). Resuscitation methods that allow VBNC cells to repair and transition into a culturable state can vary greatly depending on the type of microorganism and environmental conditions ( Bédard et al, 2014 ).…”
Section: General Stress Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Viable but non-culturable (VBNC) cells have low metabolic activity and intact membranes, but they are unable to replicate until they enter a more hospitable environment ( Ayrapetyan et al, 2018 ). Pseudomonas strains can enter this state as a response to unfavorable environmental conditions such as nutrient limitation, temperature extremes, and desiccation ( Lowder et al, 2000 ; Arana et al, 2010 ; Pazos-Rojas et al, 2019 ). Resuscitation methods that allow VBNC cells to repair and transition into a culturable state can vary greatly depending on the type of microorganism and environmental conditions ( Bédard et al, 2014 ).…”
Section: General Stress Responsementioning
confidence: 99%
“…Resuscitation methods that allow VBNC cells to repair and transition into a culturable state can vary greatly depending on the type of microorganism and environmental conditions ( Bédard et al, 2014 ). The plant growth-promoting rhizobacterium P. putida KT2440 was found to return to a cultivable state after interaction with maize root exudates or a 48 h rehydration in water ( Pazos-Rojas et al, 2019 ). The persistence of VBNC Pseudomonas in the natural environment was demonstrated with the biocontrol strain P. protegens CHA0 which survived in an uncovered field plot as a combination of dormant and VBNC cells for 72 days ( Troxler et al, 2012 ).…”
Section: General Stress Responsementioning
confidence: 99%
“…The root of each plant was placed in 50 mL conical tubes with 10 mL of sterile water for 1.5 h. To determine the bacterial population extracted from the roots, the MSDP technique was used with each selection media for each bacterium; the incubation conditions of the plates were 24 to 48 h at 30 • C (Rodríguez-Andrade et al, 2015; Molina-Romero et al, 2017). The vermiculite strongly adhered to the root was removed and its dry weight determined to calculate the parameter Colony-Forming Units / gram of Vermiculite (CFU/gV) (Morales-García et al, 2011;Rodríguez-Andrade et al, 2015;Molina-Romero et al, 2017;Pazos-Rojas et al, 2019).…”
Section: Adherence and Colonizationmentioning
confidence: 99%
“…Despite the high metabolic and adaptive versatility, the survival of P. putida decreases drastically after the loss of water [102,103]. The recent study by Pazos-Rojas and colleagues demonstrated that during desiccation, P. putida suffers damage to its membranes and enters the VBNC state, but the cells return to the culturable state after prolonged rehydration when the membranes are repaired [104]. Thus, the entering P. putida in the VBNC state could allow survival of this organism in its natural environment under conditions of desiccation.…”
Section: Mechanisms Of P Putida To Tolerate Environmental Stressmentioning
confidence: 99%